Chemical characteristics of an Ilex Kuding tea polysaccharide and its protective effects against high fructose-induced liver injury and vascular endothelial dysfunction in mice. Issue 7 (26th June 2017) - Zhai, Xichuan; Ren, Daoyuan; Luo, Yiyang; Hu, Yuanyuan; Yang, Xingbin
Abstract : The present study was designed to investigate the protective effects of Ilex Kuding tea polysaccharides (IKTP) on high fructose (HF)-induced liver injury and vascular endothelial dysfunction in mice. Abstract : The present study was designed to investigate the protective effects of Ilex Kuding tea polysaccharides (IKTP) on high fructose (HF)-induced liver injury and vascular endothelial dysfunction in mice. IKTP were identified as acidic heteropolysaccharides by FT-IR and HPLC. Healthy male Kunming mice fed 20% fructose in drinking water for 8 consecutive weeks significantly displayed dyslipidemia, hepatic steatosis, oxidative stress and vascular endothelial dysfunction. However, continuous administration of IKTP at 200, 400 and 800 mg per kg bw in HF-fed mice could prevent the damage caused by HF-diets, especially at dosages of 400 and 800 mg per kg bw ( p < 0.01). IKTP significantly reduced the HF-induced elevation of the serum TC, TG, LDL-C, TXA2 and ET-1 levels, as well as AST and ALT activities, while markedly increased the HF-induced decline of HDL-C, PGI2 and eNOS levels in the serum compared to HF-fed mice. Meanwhile, the hepatic MDA level was lowered while SOD and GSH-P x activities were increased in IKTP-treated mice, compared to HF-fed mice. Histopathology of the liver and cardiovascular aortic by H&E or oil red O staining confirmed the liver steatosis and the vascular injury induced by HF-diets and the protective effects of IKTP. These findings suggest that HF causes oxidative damage, and IKTP alleviates liver injury and vascular endothelial dysfunction.